Esoteric beliefs and opposition to Corona restrictions - Nils B. Weidmann (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2022)
Disagreement over governmental measures against the spread of the Corona virus has led to increased societal division and polarization in many countries worldwide. Scholars typically locate the sources of resistance against these measures on the right of the political spectrum. This article argues that this explanation is too simple. Using fine-grained spatial data for Germany, it tests whether opposition to Corona restrictions (proxied with electoral support for a new party against governmental Corona measures) is systematically linked to esoteric and anthroposophical beliefs, which are traditionally found on the political left. Using new data on the distribution of natural healers, homeopathic doctors and Steiner schools, the article presents spatial analyses at the level of electoral districts and municipalities. The latter makes it possible to create matched samples for improved causal inference. Results confirm that both the presence of homeopathic doctors and Steiner schools are related to significantly higher opposition against Corona measures. This shows that resistance to governmental measures against the Corona pandemic originates from different societal groups, and will remain a major challenge for governments to address.
urn:nbn:de:bsz:352-2-173n9drxps03e1
Keywords: 320